A efetivação dos direitos à saúde pública: uma análise do poder judiciário no Brasil - Carvalho, Adriana Duarte de Souza (2013)
The purpose of this doctorate thesis is to understand the achievement of the rights to public health in Brazil through the Judiciary Branch. Our hypothesis is that the constituient political actors in 1987-88 have assigned greater political power to the Judiciary Branch, turning it into a veto player, able to suspend the decisions of local executives and change the legislative status quo. Aiming the accomplishment of this research, we will study the competences of the Judiciary Branch in the constitucions of 1934 e 1946 and, afterwards, we will procede to the analysis os the Annals of the Subcomissions of the Judiciary Branch e of the Public Ministry of the Constituient of 1987-88. Eventually we will evaluate the sentences produced by the Justice Court of São Paulo to understand the content of the decisions made by the judges that managed to make effective the rightsto public health.